INNOVATIVE TEACHING EXPERIMENTS IN SCOTLAND: SHAPING THE FUTURE OF EDUCATION THROUGH PROGRESSIVE METHODOLOGIES - Shakhnoza Murakayeva; Lazokat Ikanova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. Scotland’s education system has undergone significant transformation in recent years, marked by the adoption of innovative teaching practices designed to foster a more inclusive, personalized, and engaging learning environment. These new methodologies are guided by the principles of the Curriculum for Excellence (CFE) and aim to prepare students for an ever-evolving global landscape. This article explores the latest trends in Scottish education, including the integration of active learning, the use of technology, formative assessments, and an emphasis on social and emotional learning. It also highlights how Scotland’s commitment to inclusive and sustainable practices shapes the pedagogical landscape. Through an analysis of recent reforms and evidence-based practices, this paper discusses the impact of these methods on student outcomes and the professional development of educators.